2012
DOI: 10.4038/sljpsyc.v3i1.3836
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive functions in schizophrenia: a comparative study in an Indian population

Abstract: Original paper Background Significant cognitive impairment has been considered a core characteristic of schizophrenia. Though many studies have reviewed the phenomenon, only a few Indian studies have investigated this aspect. Aims To compare the functioning of six cognitive domains of patients with chronic schizophrenia with an age, sex and education matched control group and to assess the association of socio-demographic and clinical correlates with cognitive functioning. Methods Nine different neuropsycholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Interpersonal and psychodynamic therapy assists in treating mental disease brought on by: A) Grief or loss B) Marital issues C) Changing roles, such as becoming a parent or caregiver Cognitive-behavioral therapy This kind of treatment helps people with mental illnesses identify and fix any erroneous beliefs they may have about the way the world works and about themselves. The therapist helps you create new ways of thinking by bringing to your notice both the "correct" and "wrong" beliefs you have about both yourself and other people [17,18]. People with mental illnesses that cause discomfort, impairment, or interpersonal problems, as well as those who think and behave in ways that exacerbate and prolong mental disease, should take into consideration cognitive behavioural treatment.…”
Section: Interpersonal Therapymentioning
confidence: 99%
“…Interpersonal and psychodynamic therapy assists in treating mental disease brought on by: A) Grief or loss B) Marital issues C) Changing roles, such as becoming a parent or caregiver Cognitive-behavioral therapy This kind of treatment helps people with mental illnesses identify and fix any erroneous beliefs they may have about the way the world works and about themselves. The therapist helps you create new ways of thinking by bringing to your notice both the "correct" and "wrong" beliefs you have about both yourself and other people [17,18]. People with mental illnesses that cause discomfort, impairment, or interpersonal problems, as well as those who think and behave in ways that exacerbate and prolong mental disease, should take into consideration cognitive behavioural treatment.…”
Section: Interpersonal Therapymentioning
confidence: 99%
“…Numerous studies document that schizophrenia is associated with cognitive deficits [6][7][8], but the overall degree of neuropsychological (NP) impairment varies greatly across patients [9]. In fact, a few previous studies suggest that in some schizophrenia patients, NP abilities are unimpaired or normal [10,11].…”
Section: Can Schizophrenic Be Neuropsychologically Normal?mentioning
confidence: 99%
“…Srinivasan et al (2005) reported that the neurocognitive profile of Indian patients with chronic schizophrenia resembles those of patients in developed countries 59 . Other Indian studies also reported patients with schizophrenia had significant deficits on multiple neuro-cognitive tests performance and negative symptoms predict poor performance in speed of processing and verbal working memory 58,60,61 . Impaired attentional task and Wisconsin Card Sorting Test (WCST) performances were also reported in Indian schizophrenic patient population 58,62 .…”
Section: Indian Studies On Cognitive Deficit In Schizophreniamentioning
confidence: 99%